Implementasi Kurikulum Berbasis Local Wisdom dalam Membentuk Karakter Santri di Pondok Pesantren Al-Munawwir Sangatta Selatan - Hidayah, Nur Fitri; Mubarok, Ramdanil; Jumrianah, Jumrianah (JURNAL ILMU PENDIDIKAN & SOSIAL (SINOVA), 2025)
This study examines the implementation of local wisdom values ​​in shaping students' character at the Al-Munawwir Islamic Boarding School in South Sangatta. Character education is integral to shaping the character of religious, independent, and ethical students. This study uses a qualitative approach with observation, interview, and documentation techniques. The primary informants include the head of the foundation, the head of the boarding school, and teachers/supervisors. The study results show that students' character reflects values ​​such as honesty, discipline, responsibility, politeness, and social care. Character formation strategies are carried out through daily habits, religious activities integration, and giving students roles. The obstacles faced include students' diverse backgrounds, limited facilities, and teacher adaptation to technology. However, ongoing coaching and cooperation between parties have become effective solutions in strengthening the implementation of local wisdom-based curricula.